Increased Production of Mother's Milk: Literature Review - Sri Wahyuningsih; Musviro; Ayu Dyah Maharani (KHD Production, 2023)
Introduction: Breast care is one way to release the hormone oxytocin so that breast milk is produced immediately and plays an important role in overcoming breastfeeding problems. Breast care is very important not only during pregnancy but especially after delivery to increase lactation and prevent blocked milk ducts. If left untreated, it may develop mastitis. Problems that arise when breastfeeding is not effective, so the intervention given to overcome this problem is breastfeeding education. Method: The purpose of writing this report is to determine the effectiveness of breast care to increase milk production in postpartum mothers. The method used is a literature review. The search for literature review sources was carried out from October 2021 to April 2022. The databases used were Mendeley journal, Garuda journal, and Google Scholar using the keywords Breast Care AND Breast Milk Production AND Postpartum, and obtained 873 articles. After going through the selection process and quality assessment, it was found that 10 articles that met the requirements could be included in the review. Result: In addition to breast care, breastfeeding education is also important because there are so many benefits for postpartum mothers. Breast care is effective for increasing milk production. Conclusion: Movements in breast care are useful for launching the milk ejection reflex. This activity is also an effective way to increase the amount of milk in the breast and overcome the problems that often occur during breastfeeding.